Aeromagnetic investigation of southern Calabria and the Messina Straits (Italy): Tracking seismogenic sources of 1783 and 1908 earthquakes. Issue 3 (3rd March 2016) - Minelli, Liliana; Vecchio, Antonio; Speranza, Fabio; Nicolosi, Iacopo; D'Ajello Caracciolo, Francesca; Chiappini, Stefano; Carluccio, Roberto; Chiappini, Massimo
Abstract: Southern Calabria and the NE corner of Sicily (Italy) were struck in 1783 and 1908 A.D. by two of the most catastrophic earthquakes ever in European history. Although it is generally acknowledged that the seisms were yielded by normal faults rupturing the upper crust of the Calabria‐Peloritani terrane, no consensus exists on seismogenic source location and orientation. Here we report on a high‐resolution low‐altitude aeromagnetic survey of southern Calabria and Messina Straits. In southern Calabria we document a broad weakly positive (5–10 nT) anomaly zone interrupted by three en echelon SW‐NE null to negative magnetic anomaly corridors. Euler deconvolution and magnetic modeling show that the anomaly pattern is produced by a 1–1.5 km thick crustal "layer" located within 3 km depth. This layer is offset by a 25 km long NE trending fault that corresponds to the Armo normal fault, recently inferred to be the source for the 1908 earthquake. Few kilometers to the south, we also document a subparallel and previously unrecognized fault, entering the Messina Straits and likely joining the Armo fault at depth. Further east, we model a 40 km long normal fault, probably extending northeastward for additional 40 km, running along the south Calabria axis from Aspromonte to the Serre mountains and partly following the 18 km long surface rupture witnessed by Déodat de Dolomieu after the 1783 earthquake. Thus, aeromagnetic data suggest that the sources of the 1783 and 1908 earthquakes are en echelon faults belonging to the same NW dipping normal fault system straddling the whole southern Calabria. Key Points: High‐resolution aeromagnetic survey performed in southern Calabria and Messina Straits Magnetic inversion and modeling yield an unexposed magnetic source in the upper crust Magnetics highlight the seismogenic faults of great 1783 and 1908 earthquakes